Performance of sodium pentaborate and colemanite as sources of boron for rice grown on acid and calcareous soils - Muhammad, Saleem (2010)
Boron deficiency is the most common and widespread micronutrient deficiency problem, which impairs plant growth and reduces yield. Rice is a major staple food of Asia and to keep pace with population growth, rice yields should be increased. Hence a comprehensive study was initiated to determine the soil B status in soils of the flooded rice cultivated in tropical area of Malaysia and to investigate the effectiveness of different B fertilizer sources and application rates on supplying adequate quantity of B for rice plant. Boron status study was conducted by collecting and analyzing soil samples from 15 soil series of paddy growing areas in Kedah and Kelantan states of Malaysia. Three forms of B fertilizers sodium pentaborate (SP), powder colemanite (PC) and granular colemanite (GC) were screened for their suitability as B fertilizers for flooded rice crops under acidic and calcareous soils. The effectiveness of three B fertilizers were assessed for their dissolution kinetic rates at different pH levels, B release in soil under soil incubation study and B leaching losses by conducting experiment in uniform packed soil columns. Field experiments was conducted near Alor Setar, Kedah. Four B levels (0, 1, 2, 3 kg B ha-1) in the form of SP, PC and GC were applied on rice. This experiment was continued for a second season to study the residual effect of B fertilizers on subsequent rice crop. A glasshouse experiment similar to field experiment was also conducted under high pH calcareous soil. The results indicated that the soils of paddy growing areas were very low in B status. All the soils of 15 series have available B below 0.5 mg kg-1 irrespective of depth and locations. Dissolution kinetics, soil incubation and soil column studies showed that dissolution rate of SP was higher than the other two fertilizers and pH did not have any effect on dissolution rate. There was no difference in quantity of B release from SP and PC after few weeks of application. Boron leaching losses from SP were higher than from PC and GC. Dissolution rate and solubility of GC was very slow in comparison to PC. Results of field experiment showed that application of SP and PC at 3 kg B ha-1 improved all plant growth parameters, B concentration in spikelet and rice yield over the control and other B rates. There was no yield difference in SP and PC applied plots but GC had not shown any effect on rice growth and yield. Results of our second field experiment showed that effect of residual SP, PC and GC at 3 kg B ha-1 significantly increased the plant growth and spikelet yield over the control. There was no significant difference in yield between plots with residual SP and PC fertilizers but their yields were significantly higher than plots with residual GC. The results of the glasshouse experiment under calcareous soil showed that SP and PC application at 3 kg B ha-1 produced higher yield than the 1 and 2 kg B ha-1 and there was no yield difference between ST and PC applied pots. However, application of GC had not increased the yield. Overall, results of our studies showed that Malaysian soils of paddy growing areas were deficient in available B status. SP was readily soluble and colemanite was slow release fertilizer. Sodium pentaborate and PC application significantly increased rice yield under flooded acidic and calcareous soils. Results of the study showed strong evidence of the positive residual effects of B on rice crop yield. There was no yield difference between SP and PC applied plots, both fertilizers were equally effective B sources. It was also observed that GC was ineffective B source due to non-solubility.